Religious Moderation in the Scout Movement (Gerakan Pramuka): The Role of the 2023 National Raimuna in Achieving Sustainable Development Goals Point 16 - Nunuk Hidayati; Moch. Zulkarnain Muis (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2025)
As a pluralistic nation, Indonesia continues to face challenges regarding violations of religious freedom, making strengthening religious moderation crucial to prevent extremism and build social harmony. This study analyzes the practice of religious moderation in the context of a large-scale nonformal education event, the 2023 National Raimuna of the Scout Movement, and examines its contribution to the targets of Sustainable Development Goal (SDG) 16. Using a qualitative case study approach, data were collected through open-ended questionnaires, participant observation, document analysis, and reviews of official archives. The analysis was conducted inductively using source and technique triangulation. The results show that the four indicators of religious moderation were empirically realized through structured activities such as the Beranda Nusantara forum and cultural carnival, supported by event regulations that ensured inclusivity and non-violence. These practices make significant contributions to SDG 16 targets, particularly the reduction of violence (16.1), strengthening institutional accountability (16.6), inclusive participation (16.7), and non-discriminatory policies (16. b). However, the study identified several challenges, including selective recruitment mechanisms, the temporary and controlled nature of the event, the potential for hidden resistance, and logistical capacity constraints. In response, it is recommended to develop a structured module based on religious moderation indicators for local scout units (Gugus Depan), provide dialogue facilitation competency training for mentors, implement a post-event mentoring mechanism based on personal action plans, and formulate a standard operational protocol for inclusive logistics. Further quantitative and longitudinal studies are necessary to measure the long-term impact and sustainability of value internalization.